A New Protocol for Efficient and High Yield Preparation of Nanocellulose from Elaeis guineensis Biomass: A Response Surface Methodology (RSM) Study - Yahya, Mazlita; Chen, You Wei; Lee, Hwei Voon; Chuah, Cheng Hock; Hassan, Wan Hasamudin Wan (Springer, 2019)
An innovative system for isolating nanocellulose was established that uses Ni(NO 3 ) 2 transition metal salt without the assistance of mechanical disintegrations or mineral acid and was compared with the classic production by tedious acid hydrolysis. Optimization study on Ni(II)-catalyzed hydrolysis of cellulose isolated from oil palm (Elaeis guineensis) empty fruit bunch (OPEFB) towards nanocellulose yield was investigated. Response surface methodology-central composite design was used to design and optimize the experiments with three operating parameters: pH of Ni(NO 3 ) 2 (pH 2–4), reaction time (20‒100 min) and reaction temperature (25‒65 °C). The present study indicated that the nanocellulose yield as high as 81.37% was achieved under hydrolysis conditions of pH 3, 58 °C within 58 min. At the optimum conditions, the OPEFB derived nanocellulose rendered high crystallinity of 91.1% and excellent thermal stability of 341 °C. Evidence of the successful isolation of nanocellulose was proven by HRTEM observation revealing fibrils formed the long and interconnected network-like structure with the average width of 41.1 ± 1.6 nm and several micrometers in length, which resulted in high aspect ratio. Thus, the obtained nanocellulose via Ni(II)-catalyzed hydrolysis has numerous potential applications and represent a green alternative for the treatment of OPEFB. This study provided a facile high yield procedure for the production of nanocellulose with similar characteristics to traditional nanocellulose, which was significant to the commercialization of nanocellulose. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.